Togo – 2019: Domestic politics, foreign affairs, socio-economic development - Dirk Kohnert (Africa Yearbook Volume 16: Politics, Economy and Society South of the Sahara in 2019, 2020)
Controversial constitutional and institutional reforms voted in May 2019 in parliament opened the way for President Gnassingbé to stand for a fourth and fifth term (2020 and 2030) because the law does not apply retroactively. The first local elections since more than 30 years resulted in the victory of the ruling party. Grand expectations of the opposition which had hoped for a fundamental change at least at the grass-roots were again dashed. The human rights situation sharply deteriorated due to growing political and social tensions related to the prospects of the head of state running for a fourth term. Islamist terrorist violence spread from Mali to the northern frontier region of Togo. The autonomous deep-water port of Lomé developed as a growth pole and hub for the sub-region. China became the major partner beside the established partners the EU, France and Germany. The informal sector still dominated the economy. Economic freedom remained with the overall status `mostly unfree'. – – Umstrittene Verfassungs- und institutionelle Reformen, über die im Mai 2019 im Parlament abgestimmt wurde, ermöglichten Präsident Gnassingbé eine Kandidatur für eine vierte und fünfte Amtszeit (2020 und 2030), da das Gesetz nicht rückwirkend gilt. Die ersten Kommunalwahlen seit mehr als 30 Jahren endeten mit einem Sieg der Regierungspartei. Die großen Erwartungen der Opposition, die auf einen grundlegenden Wandel zumindest an der Basis gehofft hatte, wurden erneut enttäuscht. Die Menschenrechtslage verschlechterte sich aufgrund wachsender politischer und sozialer Spannungen im Zusammenhang mit der Aussicht auf eine vierte Kandidatur des Staatschefs deutlich. Islamistischer Terror breitete sich von Mali auf die nördliche Grenzregion Togos aus. Der autonome Tiefwasserhafen Lomé entwickelte sich zu einem Wachstumspol und Drehkreuz für die Subregion. China wurde neben den etablierten Partnern EU, Frankreich und Deutschland zum wichtigsten Partner. Der informelle Sektor dominierte noch immer die Wirtschaft. Die wirtschaftliche Freiheit blieb mit dem Gesamtstatus ,,größtenteils unfrei“.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2019; domestic policy; foreign affairs; socio-economic development; period under review 2019